Self-Efficacy as a Predictor of Teachers’ Innovative Work Behavior In Medan City - Farida Siregar; Nurmaida Siregar; Andy Chandra (Jurnal Psikologi, 2026)
This study aimed to examine teacher self-efficacy as a predictor of innovative work behavior (IWB) among junior and senior high school teachers in Medan City, Indonesia. A quantitative cross-sectional predictive–correlational design was employed using purposive sampling. Participants consisted of 214 teachers from public and private schools. Teacher self-efficacy was measured using an instrument adapted from the Teacher Sense of Efficacy Scale (TSES), while IWB was assessed using a scale capturing core stages of work-related innovation, including idea generation, idea promotion, and idea implementation. All items were rated on a five-point Likert scale. Data analysis involved descriptive statistics, reliability testing, Pearson correlation, and simple linear regression. The results showed a positive and statistically significant correlation between teacher self-efficacy and IWB (r = 0.53, p < 0.001). Regression analysis further indicated that teacher self-efficacy significantly predicted IWB (β = 0.53, t = 9.09, p < 0.001), accounting for 28% of the variance in innovative work behavior (R² = 0.28, f² = 0.39). These findings demonstrate that higher levels of teacher self-efficacy are associated with greater engagement in innovation-oriented work behaviors. The results highlight the role of personal psychological resources in supporting instructional innovation, suggesting that strengthening teacher self-efficacy through practice-based professional development and organizational support may facilitate sustained innovative behavior in school settings.